On the justification of Durkheimian program in contemporary memory studies: commemorative ritual and the ambiguity of the memory - Sulzhytski, Ilya S. (Journal of the Belarusian State University. Sociology, 2019)
The article considers the importance of Durkheim’s sociology language to contemporary memory studies. It is indicated that the theme of past can be disclosed in the Durkheim’s project of social epistemology and the sociology of knowledge. In this case Durkheim’s epistemological argument can be used whis referring to the concept of time and understanding the phenomenon and commemorative rituals. It is shown that the acceleration of social life and the collapse of the temporal perspective gives rise to the so-called «Neo-tribes», that hence the multiplicity of time. Further, the article discusses the possibility of explication of the main provisions of Durkheim’s sociology of knowledge in the theoretical frame of memory studies, as well as the features of the conceptualization of such concepts as collective representations and sacred. Particular attention is paid to the phenomenon of the ambiguity of the sacred and transgression. In the conclusions is suggested the possible theoretical model in which collective memory is presented as a very significant collective representations of the past (the sacred), that are produced in commemorative practices and have internal binary logic and causality power.
Keywords: collective memory; E. Durkheim; the ambiguity of the sacred; commemorative ritual; time; collective representations